Nilai-Nilai Pendidikan Moral Kekhalifahan Umar Bin Khattab R.A Pada Buku Sejarah Kebudayaan Islam (SKI) Kelas V Madrasah Ibtida’iyah - Elisa Qotrun Nadiah; Robingun Suyud El-Syam; Nur Farida (Jurnal Kajian dan Penelitian Umum, 2024)
This research aims to determine the value of the moral education of the Caliphate of Umar bin Khattab in the fifth grade SKI book at Madrasah Ibtida'iyah, how relevant the value of moral education of the Caliphate of Umar bin Khattab is today, and the importance of moral education from an early age. This research is a type of qualitative research in the nature of library research. There are two data sources used, namely the primary data source, namely the book History of Islamic Culture for the fifth grade of Madrasah Ibtida'iyah. Then secondary data is data that provides information to data collectors indirectly, for example through other people or documents, as well as other books related to moral education and the history of Islamic culture. The data collection technique is by collecting materials that are relevant to the research and supported by other data sources that are considered to be closely related to this research. Next, data analysis in this research uses content analysis and then conclusions are drawn. Based on data analysis, it can be concluded that. The moral education values that can be taken from the Caliphate of Umar bin Khattab are honesty and trustworthiness, responsibility, caring for others, simplicity, fairness and firmness, and being firm in keeping promises. The relevance of moral education from the time of Caliph Umar until now is that it is responsive to public complaints and the culture of queuing. Abdi, Husnul, 2024, “Nilai Moral Adalah Nilai Yang Menjadi Standar Baik Aatau Buruk, Kenali Ciri-cirinya,” Liputan 6 online. 23 September 2023. https://liputan6.com/4666032/nilai-moral-adalah-nilai-yang-menjadi-standar-baik-atau-buruk-kenali-ciri-cirinya. Abdurrahman, Fuad, 2024, The Glory Story Of two Umars, Rene Islam , cet: 1: Jkarta: Rene Torus Group. Al-Qautsar, M, dan Budi Sujati, 2024, “Kepemimpinan dan Konsep Ketatanegaraan Umar Ibn Al-Khattab,” JUSPI: Jurnal Sejarah Peradaban Islam, vol. 2 no. 1 (2018). hal. 63. http//dx.doi.org/1.30829/j.v2i1.1496. Al-Qur’an Terjemah dan Asbabun Nuzul, Surakarta: Putaka Al Hanan, 2019. El-Basyiry, Abdullah Munib, 2017, Meneladani Kepemimpinan Khalifa,h, cet. 1; Jakarta: Amzah. Kantor Wilayah DKI Jakarta, 2024, “Pengaduan Melalui e-LAPOR,” http://jakarta.kemenkumham.go.id/layanan-divisi-administrasi/pengaduan-melalui-e-lapor. Mardiah, Ainun, dkk. “Narasi Mengenai Kisah Teladan Khulafaurrasyidin di Buku SKI MI,” Jurnal Penelitian, vol. 3 no. 1 (Maret 2023), hal. 184-185. http://doi.org/10.58939/afosj-las.v3i1.522. (20 Mei 2024) Muammar, 2020, Buku Siswa Sejarah Kebudayaan Islam Kelas V Madrash Ibtida’iyah, cet. 1; Jakarta: Direktorat KSKK Madrasah, Muhammad. Budiam, 2024, “Budaya Hukum Antre,” Kemenkumham 20 Juli 2017. http://jabar.kemenkumham.go.id/artikel/budaya-hukum-antre-budiman-muhammad.. Qasim A. Ibrahim dan M. A Saleh, 2014, Buku Pintar Sejarah Islam, cet. 1; Jakarta: Zaman. Qasim A. Ibrahim dan M. A Saleh, 2014, Buku Pintar Sejarah Islam, cet. 1; Jakarta: Zaman. Rubini, 2023, “Pendidikan Moral Dalam Perspektif Islam,” Jurnal Komunikasi dan Pendidikan Islam, vol. 8 no. 1 (Juni 2019), hal. 226-227. http://doi.org/10.36668/jal.v8i1.104. Sohibi, 2019, Khulafaur Rasyidin, Semarang: Penerbit Mutiara Akasara. Tulach Rahmat, Amirudin. 2023, “Penerapan Teori Albert Bandura Dalam Proses Belajar,” Jurnal At-Tarbiyah. vol.6 no. 1 (Juni 2020), hal. 48. http://doi.org/10.54621/jiat.v6i1.266. Wasito, Moh Turmudi, 2023, “Penerapan Budaya Religius Di SD Al-Mahrusiyah,” Jurnal: Pemikiran Keislaman, vo. 29 no. 1 (januari 2018), hal. 68. http://ejournal.uitlirboyo.ac.id/doi/ 10.33367/tribakti.v29i1.560..